Central neural activation following contact sensitivity peripheral immune challenge: evidence of brain–immune regulation through C fibres. Issue 2 (24th August 2015) - Thinschmidt, Jeffrey S.; King, Michael A.; Korah, Maria; Perez, Pablo D.; Febo, Marcelo; Miyan, Jaleel; Grant, Maria B.
Summary: This study tested the hypothesis that peripheral immune challenges will produce predictable activation patterns in the rat brain consistent with sympathetic excitation. As part of examining this hypothesis, this study asked whether central activation is dependent on capsaicin‐sensitive C‐fibres. We induced skin contact sensitivity immune responses with 2, 4‐dinitrochlorobenzene (DNCB), in the presence or absence of the acute C‐fibre toxin capsaicin (8‐methyl‐ N ‐vanillyl‐6‐nonenamide) to trigger immune responses with and without diminished activity of C‐fibres. Innovative blood‐oxygen‐level‐dependent functional magnetic resonance imaging data revealed that the skin contact sensitivity immune responses induced with DNCB were associated with localized increases in brain neuronal activity in treated rats. This response was diminished by pre‐treatment with capsaicin 1 week before scans. In the same animals, we found expression of the immediate early gene c‐Fos in sub‐regions of the amygdala and hypothalamic sympathetic brain nuclei. Significant increases in c‐Fos expression were found in the supraoptic nucleus, central amygdala and medial habenula following immune challenges. Our results support the idea that selective brain regions, some of which are associated with sympathetic function, process or modulate immune function through pathways that are partially dependent on C‐fibres. Together with previous studies demonstrating the motor control pathways from brain to immune targets, these findings indicate a central neuroimmune system to monitor host status and coordinate appropriate host responses.